Mancozebe influencia a persistência de fungicidas inibidores da desmetilação e inibidores da quinona oxidase em cultivares de soja - Stefanello, Marlon Tagliapietra (2017)
The soybean cultivars reaction to the causal agent of asian rust (Phakopsora pachyrhizi Syd. & P. Syd.) and mixing responsiveness of DeMethylation Inhibitor (DMI) and Quinone outsite Inhibitor (QoI) fungicides are important factors to be determined for the management of the pathogen. The activity of these fungicides sprayed on the leaves depends on the amount that it reaches the biochemical action site and the compound efficacy. Thus, the proportion of leaf deposit that it enters the leaf, the rate of entry and dissipation in the leaf tissue are determinant for the activity and diseases residual control after the occurrence of a wash. The chapter I objective was to evaluate the reaction of fifteen soybean cultivars to the causal agent of soybean rust and the responsiveness mixing Active Ingredients (AI) epoxiconazole (EPOX) + pyraclostrobin (PYR) and prothioconazole (PROT) + trifloxystrobin (TRIFL). The parameters evaluated were the latency period, residual control, progression and the Area Under the Disease Progress Curve (AUDPC). In the Chapter II, the EPOX and PYR persistence associated with mancozeb (Mz) was determined under greenhouse conditions in two commercial soybean cultivars. Artificial washes were used to determine the concentration of the remaining AI on the foliar tissues after the spraying. For this purpose, the leaves were washed with water at 0.17, 1, 2, 4, 48, 96, 192 h after the fungicide spraying and immediately collected. The EPOX and PYR concentrations were also determined on leaves at 12, 16 and 20 days after spraying. Through the high performance liquid chromatographic analysis and the experimental design, it was possible to measure the EPOX and PYR concentrations penetrated and it dissipated in whole-plant leaves, associated or not to mancozeb. The influence of the interaction between leaflets age and cultivars in the EPOX and PYR concentration on leaves after the spraying was also evaluated. Due to the scarcity of detailed studies on the performance of site-specific fungicides associated with multisite fungicides, in the Chapter III was investigated the asian rust severity and the residual control of the EPOX and PYR mixture associated mancozeb. In the chapter I, it was verified that the responsiveness of DMI and QoI mixtures to P. pachyrhizi is different among the cultivars. The greatest residual control of the pathogen in the different cultivars was through of the PROT + TRIFL spraying. In the chapter II, it was verified that mancozeb influences the persistence of DMI and QoI fungicides in soybean cultivars. The EPOX penetration rate in the cultivars was faster without the association of mancozeb to the fungicide (DMI + QoI). The association of mancozeb to the fungicide (DMI + QoI) reduced the penetration rate of PYR in DM 6563 RSF IPRO cultivar. The PYR concentration in leaves of the two cultivars at 48 h after spraying was similar by the association or not of the fungicide with mancozeb. The cultivars showed different AI penetration rates in leaves. It was observed a reduction of the AI concentrations in the foliar tissues after 48 h of the spraying, evidencing a dissipation process of the AI, after this time. The association of mancozeb to the fungicide (DMI + QoI) only influenced the persistence of PYR at 16 days after spraying in DM 6563 RSF IPRO cultivar. The dissipation rate of PYR is different between the leaves cultivars. The penetration of the AI is greater in younger leaves than in older leaves. The concentrations of PYR in soybean leaves were higher than EPOX at different sampling times, after the fungicide spraying. In the chapter III, it was verified that mancozeb associated with EPOX + PYR in spray solution increases the residual control of P. pachyrhizi and it reduces the disease severity.